2020
DOI: 10.3332/ecancer.2020.1138
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to triage among women with HPV-positive self-collection: a study in a middle-low income population in Argentina

Abstract: Introduction Screening for cervical cancer (CC) prevention has substantially changed with the introduction of human papillomavirus (HPV) tests. This technology compared to cytology has increased the detection of pre-malignant and malignant cervical lesions in real-world programmes in different settings. Very importantly, through self-collection, HPV testing can reduce barriers to screening and increase coverage. However, when using HPV self-collection, triage tests are a key step in the CC prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
2
15
0
1
Order By: Relevance
“…This is coincident with routine programmatic data from Argentina showing that adherence to triage increased with time, from 18·0% at 60 days to 42·9% at 18 months. 10 Secondly, many women who did not have triage at day 60 might be facing barriers that could not be solved by CHW visits (e.g., socio-structural barriers such as work, domestic or childcare barriers), reducing the effect of the second component on the effectiveness of the multicomponent intervention. Evidence has shown that socio-structural barriers are more difficult to address by the health system, needing intersectoral action and social participation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is coincident with routine programmatic data from Argentina showing that adherence to triage increased with time, from 18·0% at 60 days to 42·9% at 18 months. 10 Secondly, many women who did not have triage at day 60 might be facing barriers that could not be solved by CHW visits (e.g., socio-structural barriers such as work, domestic or childcare barriers), reducing the effect of the second component on the effectiveness of the multicomponent intervention. Evidence has shown that socio-structural barriers are more difficult to address by the health system, needing intersectoral action and social participation.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Though self-collection has been deemed as particularly appropriate to increase screening among socially disadvantaged women, it may actually further decrease adherence to follow-up, as women with reduced contact with the healthcare system are less likely to adhere to screening/follow-up recommendations. 10 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Efforts should be made to encourage women to follow up with treatment. It will be counterproductive if women with HIV are encouraged to participate in cervical cancer screening, but women with positive screening results are not properly managed [ 14 , 76 , 77 , 78 ]. However, the cost of treatment may discourage most women from following up, as most of these women may not have insurance or cannot afford it.…”
Section: Discussionmentioning
confidence: 99%